THE ORIGINALITY AND GENESIS OF ANIMAL SYMBOLISM IN POETRY - Urokova Nafosat Yoriyevna (Journals Park Publishing, 2023)
Uzbek poetry, a rich tapestry of cultural expression, has a history that spans centuries. Among the rich tapestry of symbolic elements employed in poetry, animal symbolism holds a special place. Animals, with their diverse characteristics, behaviors, and associations, have been used by poets throughout history to convey complex ideas and emotions. In this article, we delve into the originality and genesis of animal symbolism in poetry, tracing its roots, evolution, and significance.